Improving the strength of polyethylene solids by simple controlling of the molecular weight distribution - Kida, Takumitsu; Tanaka, Ryo; Hiejima, Yusuke; Nitta, Koh-hei; Shiono, Takeshi (Polymer (Guilford), 2021)
We prepared model polyethylene (PE) samples that contain the controlled-amounts of the high-molecular-weight component by blending a monodispersed PE into a polydispersed PE, to elucidate the influence of the high-molecular-weight component of a polymer on its mechanical properties. The strength and strain-hardening modulus were significantly enhanced by the addition of a monodispersed PE of sufficiently high molecular weight, and the critical value of Mw was determined to be ~3.0 × 105. The improved strength and strain-hardening modulus are attributed to higher amounts of inter-cluster links that bridge adjacent lamellar cluster units because these links act as stress transmitters between these units. [Display omitted] •Model polyethylene (PE) samples with different shapes of molecular weight distribution were prepared by blending mono- and polydispersed PEs.•The strength and strain-hardening modulus were enhanced by adding a high-molecular-weight component with Mw > 3.0 × 105.•The improvement of tensile properties is attributed to larger amounts of inter-cluster links, which act as stress transmitters between lamellar cluster units.